Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1994
DOI: 10.1115/94-gt-244
|View full text |Cite
|
Sign up to set email alerts
|

In Flight Heat Transfer Measurements on an Aero-Engine Nacelle

Abstract: This paper describes heat transfer measurements on the external surface of a Natural Laminar Flow (NLF) nacelle. The measurement technique employed temperature sensitive liquid crystals and platinum resistance thermometers (PRTs) to measure the surface temperature over an electrically heated pad. This gave an immediate visual indication of the transition location. The heat transfer distribution along the length of the pad has been determined and is compared with a simple theoretical model. Results are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Fig 14 is an enhanced picture of the liquid crystals temperature contours on the heater pad; the temperature gradient present at the point of laminar turbulent transition causes the liquid crystal isotherms to group together, facilitating location of transition. Analysis has shown [13] that the experimentally determined heat transfer distribution can be modelled closely and that a simple finite difference boundary layer method gives reasonable agreement; the method leads to a good estimate of the skin friction coefficients. An estimate of the drag reduction attributable to the delayed transition can be obtained using the method of Squire and Young to analyse the cold nozzle plane rake measurements; this approach has shown that a 30% drag reduction is achieved in meridianal planes which are free of installation effects.…”
Section: Nlf Nacellementioning
confidence: 98%
See 1 more Smart Citation
“…Fig 14 is an enhanced picture of the liquid crystals temperature contours on the heater pad; the temperature gradient present at the point of laminar turbulent transition causes the liquid crystal isotherms to group together, facilitating location of transition. Analysis has shown [13] that the experimentally determined heat transfer distribution can be modelled closely and that a simple finite difference boundary layer method gives reasonable agreement; the method leads to a good estimate of the skin friction coefficients. An estimate of the drag reduction attributable to the delayed transition can be obtained using the method of Squire and Young to analyse the cold nozzle plane rake measurements; this approach has shown that a 30% drag reduction is achieved in meridianal planes which are free of installation effects.…”
Section: Nlf Nacellementioning
confidence: 98%
“…Knowing the temperature distribution along the nacelle from the PRTs and liquid crystals and the corresponding input heat flux, the heat transfer coefficient can be determined for a given flight condition [13].…”
Section: Laminar/turbulent Boundary Layer Flow Transition Instrumentamentioning
confidence: 99%